Mediatization of the Quran and Internalization of Quranic Values for Children: Analysis of Instagram Da'wah @thegangoffur - Alkamala, Safira Naili; Nasrulloh, Nasrulloh (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research contains an in-depth study of internalizing values in the Al-Qur'an through social media, with a focused analysis of the da'wah content presented via the Instagram account @thegangoffur. Specifically, this research aims to classify the delivery of da'wah messages based on the logical design of the message and analyze the formulation of the internalization of the values contained. This research uses qualitative research methods with content analysis methods. Data collection through literature study on data sources in the form of uploading preaching content on the Instagram account @thegangoffur. Data analysis techniques use the Miles, Huberman, and Saldana models. The theory used is message logic design by Barbara O'Keefe, divided into three studies: expressive, conventional, and rhetorical. The research results show that: First, expressive logic is designed with an informal and emotional language style, such as exclamation marks and expressions that reflect decisions and beliefs about patience and time management; Second, conventional logic is designed with a semi-formal language style and excerpts from Qur'anic verses. The da'wah message contained includes understanding the nature of Allah as All-Seeing. Third, rhetorical logic uses interrogative sentences and persuasive sentences that reflect readers on their beliefs about the concept of tawakkal. The urgency of this research is because it shows the potential of social media as an effective means of spreading Islamic values and bringing the teachings of the Al-Qur'an closer to the broader community in a modern and interactive way.